Cognitive behavior therapy for academic burnout, procrastination, self-handicapping behavior, and test anxiety among adolescents: a randomized control trial - Khizra Khurshid; Rabia Mushtaq; Umara Rauf; Nida Anwar; Qasir Abbas; Sumayah Aljhani; Zoobia Ramzan; Mafia Shahzadi (BMC Psychology)
Abstract Objective Academic stressors among adolescents, strongly associated with emotional disturbance, increase the chance of psychiatric problems, and their severity increases over time when emotional and educational issues remain unresolved. The present study is designed to investigate the impact of cognitive behavioural therapy (CBT) on procrastination, burnout, self-handicapping behaviour, test anxiety, and school functioning among adolescents facing academic problems. Materials and methods A total of 200 adolescents were enrolled for eligibility assessment; 129 participants met the eligibility criteria, and they were allocated to the experimental and waitlist control conditions. After the baseline assessment, participants were involved in the treatment condition, and after 6–8 follow-up sessions, they were referred for the post-assessment. We used different assessment measures to assess the outcome, i.e. General Procrastination Scale (GPS), Maslach Burnout Inventory-Student Survey (MBI-SS), Self-handicapping Scale (SHS), Test Anxiety Inventory (TAI), and Living up to Parental Expectation Scale (LPES). Repeated measures ANOVA was used to analyze the results. Results The current RCT findings suggest that CBT was found an effective treatment condition to address the emotional problems among adolescents. CBT significantly reduced the degree of procrastination {F (1, 63) = 25.01, p < .000, η 2 = 0.29} academic burnout {F (1, 63) = 11.08, p < .000, η 2 = 0.16}, test anxiety {F(1, 63) = 88.17, p < .000, η 2 = 0.59}, and self-handicapping {F (3, 56) = 10.17, p < .000, η 2 = 0.16} among adolescents. CBT also significantly helped the students to manage parental unrealistic expectations through providing relationship skills and training {F (3,56) = 546.46, p < .001, η 2 = 0.89). Further analysis reveals that counseling sessions substantially improved students’ academic performance and students functioning at school in term of attendance and punctuality. Conclusion It is concluded that CBT efficiently addressed emotional and academic problems (i.e. procrastination, burnout, test anxiety, and self-handicapping behavior), improved students’ functioning at school (i.e. attendance & and academic grades), and guided the students to manage unrealistic parental expectations.